Visioning services for children affected by HIV and AIDS through a family lens - Richter, Linda (The International AIDS Society, 2010)
The HIV epidemic continues to place a great burden on children, from loss of parents and income to severe disruptions of their homes and families. Underpinned by the understanding that a healthy family constitutes the foundation for a child's wellbeing, the importance of family-centred care and services for children is increasingly recognized. It is not enough to merely provide antiretrovirals: it is of pivotal importance that treatment and care for children are integrated into the broader context of family-support schemes. However, despite growing evidence of the benefits of family-centred services, reforms in favour of family oriented HIV interventions have been slow to emerge. Treatment, prevention and care interventions often target individuals, and not families and communities. For the first time, this supplement to the Journal of the International AIDS Society brings together in one place the rationale for family-centred services for children affected by HIV and AIDS and some of the available evidence for the effectiveness of doing so. We hope this constitutes a beginning of what could be a groundswell of interest in family-centred services for children affected by HIV and AIDS.